ANALISIS PENGARUH MARKETING MIX TERHADAP PERSEPSI KONSUMEN PLATINUM CERAMICS INDUSTRY Ltd SURABAYA. - Halik, Abdul (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2010)
The ceramic floors are the products which are used for house floors and have an art touching. The ceramic mosaics are prepared by the company, for public to fulfill the housing needs. So one consumer with the other consumer has different perception of the product, price, distribution and promotion. For that reason we need to know the influence of marketing mix to the consumer perception for the good and bad of Platinum Ceramics Industry Ltd, so we will know how the influence of marketing mix to the consumer perception of Platinum Ceramics Industry Ltd. The understandingof this problem is important for the marketer, as a basic making of effective marketing strategic. The that reason this research is for knowing the marketing mix influence to the consumer perception about the good and bad of Platinum Ceramics Industry Ltd, and the most dominant variable.According to the consumerÂ  behaviour theory which consist of buyer characteritic which must be paid attention by the marketer, so there is a possibility of marketing mix influence to the consumer perception. Baside that, there is marketing mix variable which has the most dominant influence to the consumer perception.This research is done to the mosaic ceramic consumers with the brand Platimun which has needs and wants with the research object target in Surabaya. The amount of respondens which are used for samples are 100 people, the sampling method which is used is the convenience method, the samples are the ones which are easily met and in coincidence surveying at the mosaic ceramic. The data collections are done by iterviewing and spreading the questionairs. The results of the research are : (1) There is an influence of partial marketing mix variable to the consumer perception about the good and bad of Platinum Ceramics Industry Ltd Surabaya. (2) There is an influence of marketing mix variable together to the consumer perception about the good and bad Platinum Ceramics Industry Ltd Surabaya. (3) The price variable is the most dominant influence. The conclusion which is got is the marketing mix has positive influence to the consumer perception about the good and bad of Platinum Ceramics Industry Ltd Surabaya.The marketing mix analization like above can give the implication to the marketing strategy, especially for making aand deciding the marketing mix strategy of Platinum Ceramics Industry Ltd Surabaya.Key word : Â The influence of marketing mix to the consumer perception for the good and bad.